Clinical value of C-reactive protein to albumin ratio, aspartate aminotransferase, and platelet-to-lymphocyte ratio in predicting the severity of community-acquired pneumonia in children - Han, Bo; Li, Xiang; Zhang, Lu; Zhang, Hao; Wang, Bo (Frontiers in Pediatrics, 2025)
Background/objectivesCommunity-Acquired Pneumonia (CAP) is a common acute and critical illness in pediatrics and one of the leading causes of death in hospitalized children worldwide. Inflammatory mechanisms play a significant role in pneumonia, and inflammatory markers have shown value in predicting severity in various diseases. This study aimed to explore the predictive value of key inflammatory markers for identifying the severity of pediatric CAP.MethodsA retrospective analysis was conducted on children with CAP, comparing inflammatory markers between mild and severe pneumonia groups. Markers analyzed included Platelet-to-Lymphocyte Ratio (PLR), Aspartate Aminotransferase (AST), and C-Reactive Protein to Albumin Ratio (CAR). Statistical analyses involved group comparisons using appropriate tests for continuous and categorical variables, multivariate logistic regression to identify independent risk factors, and receiver operating characteristic (ROC) curves to evaluate predictive performance (p < 0.05 considered significant).ResultsA total of 303 children were included; 87 with severe pneumonia and 216 with mild pneumonia. Severe cases showed significantly higher levels of CAR (24.52 vs. 0.19 mg/L, p = 0.004), AST (37.67 vs. 7.85 U/L, p = 0.040), and PLR (162.83% vs. 126.55%, p = 0.042) compared to mild cases. Logistic regression confirmed CAR (OR = 1.052, 95% CI: 1.004–1.102, p = 0.004), AST (OR = 1.087, 95% CI: 1.064–1.111, p = 0.002), and PLR (OR = 1.046, 95% CI: 0.996–1.099, p = 0.033) as independent risk factors for severe CAP. ROC analysis showed AST had the highest discriminative power (AUC = 0.837, sensitivity = 78%, specificity = 85%), followed by CAR (AUC = 0.797) and PLR (AUC = 0.721).ConclusionsHigh levels of CAR, AST, and PLR are significantly associated with the presence of severe pneumonia in children with CAP and can serve as effective predictive indicators for identifying disease severity and guiding clinical assessment of disease progression.